Inflexibility and Stock Returns - Gu, Lifeng; Hackbarth, Dirk; Johnson, Tim (Review of Financial Studies, 2018)
Investment-based asset pricing research highlights the role of irreversibility as a determinant of firms' risk and expected return. In a neoclassical model of a firm with costly scale adjustment options, we show that the effect of scale flexibility (i.e., contraction and expansion options) is to determine the relation between risk and operating leverage: risk increases with operating leverage for inflexible firms, but decreases for flexible firms. Guided by theory, we construct easily reproducible proxies for inflexibility and operating leverage. Empirical tests provide support for the predicted interaction of these characteristics in stock returns and risk.